Developing an underlying inflation gauge for China - Marlene Amstad; Huan Ye; Guonan Ma (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
Inflation in emerging markets is often driven by large, persistent changes in food and energy prices. Core inflation measures that neglect or under-weight volatile CPI subcomponents such as food and energy risk excluding information helpful in assessing current and future inflation trends. This paper develops an underlying inflation gauge (UIG) for China, extracting the persistent part of the common component in a broad dataset of price and non-price variables. Our proposed UIG for China avoids the excess volatility reduction that plagues traditional Chinese core inflation measures. When forecasting headline CPI, the proposed UIG outperforms traditional core inflation measures over a variety of samples.
URN:NBN:fi:bof-201805081497
Keywords: C13; C33; E31; E37; G15; C43; 330